(untitled) (Research, Society and Development, 2022)
Introduction: Viral infections affect oxidative metabolism and may have repercussions on mitochondrial alterations, compromising cellular homeostasis. Objectives: To assess mitochondrial bioenergetics and oxidative balance in in vitro arbovirus infection models. Methods: The review was written in accordance with the PRISMA and submitted to the Open Science FrameWork platform with DOI 10.17605 / OSF.IO / 8ZFSW. Were used the Descriptors/MeSH (Arbovirus, Arboviruses, Arbovirus infections, Mitochondria, Oxidative stress and Reactive oxygen species) was carried out on the platforms: PubMed, SCOPUS, COCHRANE, Lilacs and Web of Science. The quality analysis of the studies was performed using the ARRIVE tool adapted to the CONSORT, followed by the KAPPA concordance test, were used 24 articles. Results: Results show morphological alterations in the mitochondria, such as swelling, fragmentation, and the appearance of membranes. Mitochondrial stretching was more intense in regions close to the convoluted zones, associated with changes in the genes of mitochondrial dynamics. Changes in oxidative stress biomarkers, antioxidant enzymes and ROS production were evident in most articles, except for those that used cells of immunological origin. Conclusion: Changes in mitochondrial bioenergetic can assist the virus in the replication process, however, these changes can result causing damage cell and of oxidative stress.